2017
DOI: 10.1590/1516-4446-2016-2152
|View full text |Cite
|
Sign up to set email alerts
|

Childhood emotional and behavior problems and their associations with cesarean delivery

Abstract: Objective: To determine the prevalence of childhood emotional and behavioral problems and examine their associations with cesarean delivery. Methods: Our sample consisted of 8,900 preschoolers from 35 kindergartens in four cities in East China. Parents completed the Strengths and Difficulties Questionnaire (SDQ) and provided other information. Children's emotional and behavioral problems were assessed using five subscales of the SDQ. Mode of delivery was classified as vaginal or cesarean section (CS); in sub-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 38 publications
(48 reference statements)
1
21
0
2
Order By: Relevance
“…A study of approximately 11 000 Irish children found CS delivery to be associated with a delay in personal social skills at 9 months (odds ratio of 1.24 214 ). In a study of early childhood in China, any CS delivery was associated with abnormal pro‐social behaviour (odds ratio of 1.27) and emergency CS was associated with peer problems (odds ratio of 1.25 231 ). However, such effects were not seen in a British cohort using a slightly less sensitive checklist 232 .…”
Section: Known Associations Of Caesarean Delivery With Developmental mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of approximately 11 000 Irish children found CS delivery to be associated with a delay in personal social skills at 9 months (odds ratio of 1.24 214 ). In a study of early childhood in China, any CS delivery was associated with abnormal pro‐social behaviour (odds ratio of 1.27) and emergency CS was associated with peer problems (odds ratio of 1.25 231 ). However, such effects were not seen in a British cohort using a slightly less sensitive checklist 232 .…”
Section: Known Associations Of Caesarean Delivery With Developmental mentioning
confidence: 99%
“…230 214 ). In a study of early childhood in China, any CS delivery was associated with abnormal pro-social behaviour (odds ratio of 1.27) and emergency CS was associated with peer problems (odds ratio of 1.25 231 ). However, such effects were not seen in a British cohort using a slightly less sensitive checklist.…”
Section: Emotion and Mental Healthmentioning
confidence: 99%
“…The Microbiota-Gut-Brain-Axis concept is gaining relevance and recent scientific evidences suggest an important role of the gut microbiota in brain processes. In this way, some works have linked the effect of CS with the incidence of neuropsychiatric disorders [36] or risk of behavioural problems [37]. More investigations are needed to confirm the relationship between CS, gut microbiota and brain function, in order to design nutritional strategies helping at the establishment of a correct microbiota-gut-brain axis connection in early life.…”
Section: Perspectives and Future Trends On The Research About The Relmentioning
confidence: 99%
“…; Rutayisire et al . ). The concept stemmed from an interesting series of animal studies on CS (± anoxia exposure post‐birth) (Boksa & El‐Khodor, ) and has promoted an ongoing debate as to whether childhood emotional and behavioural problems may be increased in children delivered by CS.…”
Section: Introductionmentioning
confidence: 97%